Opportunities and Challenges of Social Forestry Programs in the KHDPK Area (Case Study in Pati Regency, Central Java Province) - Julia Aura Zakia; Ghazy Zhafiri Taufiqul Hafiz; Jihan Ismahwat; Mafut Munajat; Supriyadi; Ana Agustina (Jurnal Ilmu Ilmu Kehutanan, 2024)
Social forestry is defined as a forest management system, both in state forests and private forests that involve local communities as the main actors in forest management. This research was conducted to find out what opportunities and challenges are in the management of Special Management of State Forest (KHDPK) in Social Forestry scheme in Pati Regency. This research is descriptive exploratory with a qualitative approach. Primary data was obtained from interviews with key informants and field observations. Secondary data was obtained from literature studies and document studies from related agencies. Data analysis is carried out by Exploratory Descriptive method supported by the presentation of data in the form of images, graphs and diagrams. The results of this study can be reported that Pati Regency has 9 social forestry groups that have received a decision letter. The opportunity to implement Social Forestry and KHDPK in Pati Regency is that farmers get free access to manage land so that they can improve farmers' welfare. The challenge of social forestry management and KHDPK in Pati Regency is the low human resources of farmers which can cause conflicts and hinder the implementation of this program. There needs to be assistance and counseling for forest farmers and communities around the forest regarding the model of optimal forest management that is in accordance with the principles of ecosystem sustainability and concordant to soil and water conservation.